Isolation and structure identification of new alkaloids from the sponge Rhabdastrella rowi - Hertiani, Triana; Edrada, RuAngelie; Van Soest, Rob W.M.; ., Sudarsono; Proksch, Peter (INDONESIAN JOURNAL OF PHARMACY, 2008)
Chemical investigation on marine sponge Rhabdastrella rowi collected from Bali, Indonesia has been performed. This study was aimed to isolate and to identify structures of the sponge secondary metabolites as well as to test their cytotoxicity activity on mouse lymphoma cell line L5178Y.Isolation procedure was performed by using different chromatography techniques. NMR spectroscopy and mass spectrometry methods were used to identify the compounds chemical structures. Cytotoxicity of the isolates was tested on mouse lymphoma cell line L5178Y by using the microculture tetrazolium (MTT) assay.This study yielded two new alkaloids, quinolin-4-ol (1) and quninazolin-4-amine (2) which were found as minor constituents of Rhabdastrella rowi. Both compounds were observed as inactive against mouse lymphoma cell line L5178Y.Key words: Rhabdastrella rowi, sponge, alkaloids